2014
DOI: 10.1016/j.jempfin.2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

High frequency lead/lag relationships — Empirical facts

Abstract: Lead/lag relationships are an important stylized fact at high frequency. Some assets follow the path of others with a small time lag. We provide indicators to measure this phenomenon using tick-by-tick data. Strongly asymmetric cross-correlation functions are empirically observed, especially in the future/stock case. We confirm the intuition that the most liquid assets (short intertrade duration, narrow bid/ask spread, small volatility, high turnover) tend to lead smaller stocks. However, the most correlated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 23 publications
(43 reference statements)
4
71
0
Order By: Relevance
“…They also investigated the enlarged correlation matrix obtained from original and lagged indices and examine a network structure derived from it, thus showing connections between lagged and original indices that could not be well represented before. Huth and Abergel (2014) confirmed that the intuition that the most liquid assets (short inter-trade duration, narrow bid/ask spread, small volatility, high turnover) tend to lead smaller stocks. These lead/lag relationships become more and more pronounced as we zoom on significant events.…”
Section: Literature Reviewsupporting
confidence: 68%
“…They also investigated the enlarged correlation matrix obtained from original and lagged indices and examine a network structure derived from it, thus showing connections between lagged and original indices that could not be well represented before. Huth and Abergel (2014) confirmed that the intuition that the most liquid assets (short inter-trade duration, narrow bid/ask spread, small volatility, high turnover) tend to lead smaller stocks. These lead/lag relationships become more and more pronounced as we zoom on significant events.…”
Section: Literature Reviewsupporting
confidence: 68%
“…Hayashi and Yoshida (HY) discuss the problem of non-synchronous trading in terms of the errors that can arise when randomly spaced observations like trade arrivals are sampled at regular time frequencies. Huth and Abergel (2014) and Hoffmann, Rosenbaum, and Yoshida (2013) use the lagged version of the HY estimator to devise a lead/lag ratio where the lags may be dependent and assess whether one variable leads or lags another. In contrast, the HY cross-correlation estimator makes use of all data, regardless of the time intervals between samples, and thereby deals with the issues of non-synchronous trading and spurious correlations without a need to rely on sampling.…”
Section: Intraday Return Analysis Test Methodologymentioning
confidence: 99%
“…This implies that the pairwise causal link between the leading and lagging contracts deteriorates throughout the day (Huth and Abergel, 2014). This implies that the pairwise causal link between the leading and lagging contracts deteriorates throughout the day (Huth and Abergel, 2014).…”
Section: The Intraday Profile Of Lead-lag Relationshipsmentioning
confidence: 99%
“…7 A similar procedure is performed in Huth and Abergel (2014). If one monitors changes in the mid-quote, the first scenario will always yield a non-zero return, while the second scenario will always yield a zero return.…”
Section: Futures Contracts Datamentioning
confidence: 99%
See 1 more Smart Citation